Hearing Protection Device Use Behaviors and Personal Attenuation Rating (PAR) among Production Workers in an Electrical Appliance Component Factory in Chonburi Province - Chiamchunya, Arutchaporn; Kulwong, Saksith; Thetkathuek, Anamai (Disease Control Journal, 2026)
This cross-sectional analytical research aimed to study: 1) hearing protection device (HPD) uses behaviors, 2) Personal Attenuation Ratings (PAR), and 3) the association between HPD use behaviors and PAR. The study participants were 120 production workers at an electrical appliance manufacturing company in Chonburi province. Data was collected from July to August 2025 using a self-administered questionnaire, an HPD use behavior observation form, and the hearing protection fit-testing system. Data was analyzed using descriptive statistics and binary logistic regression analysis. The results showed that the majority of workers were male (87.5%) and aged 30-39 years (43.3%). While 81.7% of workers regularly wore HPDs when exposed to loud noise, only 22.5% performed HPD maintenance correctly. The median PAR was 17 dB (IQR(Q1-Q3):9(11-20)). A total of 81.7% of workers achieved a PAR greater than or equal to the Target PAR. Workers who did not regularly wear HPDs with a proper tight fit had 4.28 times higher odds of having an inadequate PAR compared to those who did (AOR=4.28, 95% CI: 1.53-11.95). However, 18.3% of workers had a PAR below the target, which could lead to hazardous noise exposure and long-term noise-induced hearing loss. Therefore, workplaces should emphasize correct HPD wearing and provide training on both usage and maintenance. Additionally, relevant agencies should establish a policy for hearing protection fit testing to effectively reduce the risk of occupational noise exposure.